2009
DOI: 10.1111/j.1742-7843.2009.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade Herbal Products and Induction of CYP2C19 and CYP2E1 in Cultured Human Hepatocytes

Abstract: The aim of this study was to evaluate in vitro the dose-dependent induction potential of six commonly used trade herbal products on CYP2C19 and CYP2E1 metabolic activities in cultured human hepatocytes. S-mephenytoin and chlorzoxazone were used as specific CYP substrates, respectively, and rifampicin was used as a positive induction control for both enzymes. The hepatocytes were exposed to herbal extracts in increasing and biological relevant concentrations for 72 hrs and CYP substrate metabolites were quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The authors conclude that both CYP 3A4 and P-gp interactions are unlikely to be clinically relevant, as the systemic concentrations are probably much lower; therefore, respective IC 50 values for P-gp cannot be reached in vivo. This conclusion is also applicable to their previous study [36] and to their study on CYP 2C19, which showed a weak induction by valerian root extracts [47].…”
Section: In Vitro Studiessupporting
confidence: 51%
“…The authors conclude that both CYP 3A4 and P-gp interactions are unlikely to be clinically relevant, as the systemic concentrations are probably much lower; therefore, respective IC 50 values for P-gp cannot be reached in vivo. This conclusion is also applicable to their previous study [36] and to their study on CYP 2C19, which showed a weak induction by valerian root extracts [47].…”
Section: In Vitro Studiessupporting
confidence: 51%
“…[38][39][40][41] Phenobarbital is a typical enzyme inducer of CYP2C9 and CYP3A4, which presents a weak induction effect (20-50% decrease in substrates' AUC) .38,42-44 Several studies have shown that repeated doses of efavirenz and St John's wort had a significant induction effect on both CYP2C19 and CYP3A4 in vivo. [45][46][47][48][49][50][51][52][53] Thus, in our study these two drugs may enhance voriconazole metabolism through the induction of the above enzymes. In previous studies, ritonavir has been found to be a potent inhibitor of CYP3A4.…”
Section: Explanation For Findingsmentioning
confidence: 71%
“…They also studied the induction capacity of some herbal drugs on CYP1A2, CYP2D6, CYP2C19, CYP2E1 and CYP3A4 metabolic activities in cultured human hepatocytes and reported that Ginkgo biloba may exert opposite and biphasic effects on CYP1A2, CYP2C19, CYP2E1 and CYP2D6 metabolic activities. Induction of CYP1A2, CYP2C19, CYP2E1 and inhibition of CYP2D6 were found at low concentrations; the opposite was observed at high concentrations (64,102). They reported that inducing effect of Ginkgo biloba was close to that of SJW.…”
Section: Yeung Et Al (2009) Have Investigated the Effect Of Ethanol mentioning
confidence: 85%
“…Hellum et al (2009) reported that among the herbal drugs they studied, SJW was the most potent CYP-modulating herb, showing a dose-dependent induction/inhibition of both CYP2C19 and CYP2E1, with induction at low dosages and inhibition at higher (64).…”
Section: St John's Wort (Sjw) (Hypericum Perforatum)mentioning
confidence: 99%